Επίδραση διαφορετικών επιπέδων αλατότητας σε έδαφος και σε υδροπινική καλλιέργεια - Σολωμού, Μαρία (Τμήμα Γεωπονικών Επιστημών, Βιοτεχνολογίας και Επιστήμης Τροφίμων, Σχολή Γεωτεχνικών Επιστημών και Διαχείρισης Περιβάλλοντος, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Salinity is a major stress factor, since when in high concentrations adversely affects the growth, size, quality and quantity of crop production. Therefore, the aim of this study is to investigate the effect of different concentrations of salinity on growth of spearmint growing in the ground, and in a closed hydroponic system (Deep Flow Technique). Treatments were applied 3 mM, 25 mM, 50 mM, 100 mM NaCl in the nutrient solution and soil. The experiment examined different plant growth parameters such as the number of leaves, number of shoots, length larger sheet, root length, fresh and dry weight of root, fresh and dry weight of aerial parts, plant height. Additionally, stomatal conductance, the concentrations of N, P, K, Na and the fluorescence of chlorophyll were determined. The results showed that the growth of plants in hydroponic culture was significantly more robust than in the ground. It was also observed that in the implementation of maximum salinity (100 mM NaCl) there was a significant decrease, among others, in the number of leaves (42 % in hydroponics and 29 % in soil), the number of shoots (30 % in hydroponics and 50 % in soil). Regarding stomatal conductance and the Na concentration in hydroponic culture, the application of 100 mM NaCl increased greatly, compared with the other treatments. The root length, dry weight of root and aerial parts, nitrogen concentration and the fluorescence of chlorophyll (in hydroponics and soil) showed no significant change between treatments. The measurements such as the length of the largest leaf, fresh weight of root and aerial parts, plant height and concentrations K and P, for the plants in soil, showed no particular change, but decreased in plants of hydroponic cultivation.
Keywords: Hydroponic; Soil; Salinity; Mentha spicata; Υδροπονία; Έδαφος; Αλατότητα; Δυόσμος